EXPERIENCE WITH RITUXIMAB IN PATIENTS WITH ANKYLOSING SPONDYLITIS - Mikhail Sergeyevich Protopopov (Научно-практическая ревматология, 2013)
Objective: to analyze the efficacy of rituximab (RTM) in patients with active ankylosing spondylitis (AS) resistant to conventional therapy. Subjects and methods. The trial enrolled 10 male patients with the reliable and valid diagnosis of AS who received therapy with RTM used in cases of steadily high AS activity, resistance to standard therapy, and contraindications to the use of tumor necrosis factor-α inhibitors. The number of patients meeting the Assessment of Spondyloarthritis International Society (ASAS) criteria for 20% improvements 24 weeks after treatment initiation was the main indicator of therapeutic effectiveness. Results. After 24-week therapy, 7 and 4 of the 10 patients showed 20 and 40% improvements, respectively; and 2 patients had partial remission according to the ASAS criteria. During the treatment, the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) significantly decreased (p = 0.046), the Bath Ankylosing Spondylitis Functional Index (BASFI) remained substantially unchanged. Treatment response did not depend on the development of an early (at 2 weeks) complete depletion of CD20 lymphocytes. No significant effect could be achieved in patients with high baseline BASDAI and BASFI scores. Conclusion. RTM used patients with AS can ensure clinical improvement and even remission in a number of cases; however, it is unpromising in cases of high disease activity and severe functional failure.